Gambaran Self-Acceptance Bagi Perempuan Hamil di Luar Nikah Ditinjau dari Perspektif Teori Germer - Hasibuan, Tama Sentia; Sahputra, Dika (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The study uses Germer's theory to discover the self-acceptance experienced by women who become pregnant out of wedlock. The research design selects qualitative descriptive studies. The subjects used were three informants, and the object of the researcher was a woman who experienced pregnancy out of wedlock. Data were collected through semistructured interviews conducted by observation, interviews, and documentation. The results showed that in the three subjects through self-acceptance of Germer's theory, the stages of self-acceptance that were passed were; First, Evasion. At this stage, in three of the two clients, some do avoidance because they feel afraid of their parents. And one of those clients did not evade because he considered it a waste of time. The second is curiosity. At this stage, one in three clients has found out about her pregnancy because she wants to see her parents' sensitivity to the complications she has experienced, such as nausea. Meanwhile, two clients never learned about his condition because he thought it would add pressure to them—subsequent third tolerance. Here the three clients appreciate the health they experience by maintaining their respective contents. Then fourth, allowing. At this stage, the client can feel unencumbered about people's ridicule or ridicule of their situation by not listening too much, as it will be detrimental to them. And lastly, friendship. At this stage, the client can receive the condition because of the support of the spouse, family, and friends, so the three subjects can accept their situation as a whole.